2008
DOI: 10.1016/j.tetlet.2008.02.120
|View full text |Cite
|
Sign up to set email alerts
|

The facile synthesis of a series of tryptophan derivatives

Abstract: Further information on publisher's website:http://dx.doi.org/10. 1016/j.tetlet.2008.02.120 Publisher's copyright statement:Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 11 publications
0
34
1
2
Order By: Relevance
“…They also mentioned that N, O-diacetylserine (14) was obtained as a major product from the reaction of 2 and Ac 2 O, without the formation of 8. In contrast, in our NMR experiments, there is no evidence for the formation of 14 or intermediate 11: there are no signals other than those due to 6, 7, 8 and 9 in the reaction mixture of 6 with Ac 2 O-d 6 in AcOH-d 4 , even after 60 min, as shown in Fig. 2C.…”
Section: Resultscontrasting
confidence: 68%
See 3 more Smart Citations
“…They also mentioned that N, O-diacetylserine (14) was obtained as a major product from the reaction of 2 and Ac 2 O, without the formation of 8. In contrast, in our NMR experiments, there is no evidence for the formation of 14 or intermediate 11: there are no signals other than those due to 6, 7, 8 and 9 in the reaction mixture of 6 with Ac 2 O-d 6 in AcOH-d 4 , even after 60 min, as shown in Fig. 2C.…”
Section: Resultscontrasting
confidence: 68%
“…Although all spectral data showed that our proposed mechanism is rational, Sanderson [4] proposed a different mechanism (Scheme 4). They concluded that the cationic species (11) derived from N,O-diacetylserine (14) is the key intermediate which is reactive in nucleophilic substitution reactions, and that 11 equilibrates to N-acetyldehydroalanine (8).…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…In contrast, the use of halotryptophans as substrates in Suzuki-Miyaura couplings was initially hampered by their limited commercial availability (NB: pseudohalogenated tryptophans and derivatization thereof have not been reported to date). Chemical synthesis of these building blocks often lack generality and require specific procedures for each regioisomer [70][71][72][73]. In view of this issue, a straightforward procedure for the enzymatic synthesis of halogenated tryptophans was described via use of tryptophan synthase on the corresponding readily available indole analogues [37,74].…”
Section: Access To and Derivatization Of (Pseudo)halogenated Aromaticmentioning
confidence: 99%